Students' perceptions of health informatics learning: a survey of Jordanian and Palestinian students in health-related disciplines. (March 2019) - Khader, Yousef; Alzyoud, Sukaina; Jabareen, Hussein; Awad, Samah; Abu Rumeileh, Niveen; Manasrah, Nemeh; Modallal, Rolla; Taweel, Adel
Abstract: Background: Training for health students is essential to equip them with health informatics competencies and skills. This study used a tailored version of the technology acceptance model (TAM) to assess Jordanian and Palestinian students' attitudes and thoughts regarding learning of health informatics, to determine their intention to learn, to assess the required skills for health informatics, and to determine reasons that could motivate students to study health informatics. Methods: A descriptive, cross-sectional study was conducted among senior undergraduate students in health-related disciplines in four universities in Jordan and Palestine. A stratified random sample of 1000 students was emailed the link to the web-based questionnaire and requested to complete the questionnaire on a voluntary basis. According to the recommendation by Comrey and Lee (1992), the sample size should be more than 500 to be able to perform factor analysis. The questionnaire included questions on the TAM construct. A five-point Likert-type scale was used to record responses to the questions. Findings: A total of 891 students responded to the study questionnaire; a response rate of 89%. The majority (83%; 737 of 891) of students were interested in learning health informatics. Approximately 63% (560 out of 891) of students reported that they would take a set of health informatics courses during their undergraduate degree if given such an opportunity. Approximately 70% (624 of 891) of students perceived health informatics learning as useful. Only a third of students (36%; 322 of 891) believed that their university provides a supportive environment for health informatics programmes. Approximately 75% (668 of 891) of students had the intention to enter the health informatics programme, and reported that they were enthusiastic about the use of health information technology in patient care in future medical practice. Interpretation: Understanding students' perception and acceptance of health informatics learning is very important to predict the adoption and implementation of these applications during practice. Students perceived health informatics learning as useful and easy, had a positive attitude towards health informatics, and a strong intention to learn health informatics. The results of this study provide directions for the implementation of health informatics education. Funding: This study, part of the HiCure project, has been funded with support from the European Commission and the European Union's Erasmus+ programme.